The Ameliorative Effects of Phyllanthus gomphocarpus Hook. F. on Sperm Parameters of Rats Induced with Bisphenol A - Kamarudin, Evana; Dasiman, Razif; Bahari, Ebby Anuar; Daud, Kamalru Azman; Suwandi, Nur Rohmah (Majalah Obat Tradisional, 2023)
Infertility due to poor sperm quality is a common problem nowadays, particularly in developed countries. Herbs are one of the natural treatment options that have been proposed. Phyllanthus gomphocarpus Hook. F is a tropical plant that has traditionally been used in Malaysia to treat male infertility. Antioxidant characterization of its root aqueous extraction was performed using ferric reducing antioxidant power (FRAP), 1,1-diphenyl-2-picrylhydrazyl (DPPH), total phenolic content (TPC), and total flavonoid content (TFC). Male rats were administered two different concentrations of the extract orally along with BPA for 21 days, and their sperm was evaluated using Computer-Assisted-Sperm-Analysis (CASA). The results showed that this plant has a high antioxidant capacity, with 78.6 ± 0.65 %, 0.14 ± 0.01 mg/ml, 28.52 ± 0.13 mg GAE/g and 164.73 ± 23.13 mg QE/g, for DPPH, FRAP, TPC and TFC respectively. The ability of this plant to enhance sperm concentration, motility, velocity, progression ratio, elongation, and percentages of normal sperm morphology significantly with p<0.05, appears to be due to its high antioxidant capacity. Furthermore, this plant was found to have sperm-protective effects against the endocrine disruptor BPA. A thorough investigation is required to determine the full mechanism of this plant's beneficial effects on male fertility and human health.